ESTRUS DURATION AND EXPRESSION IN NATURAL AND INDUCED ESTRUS IN INDIGENOUS (B os indicus) CATTLE - B. Shahid; M. I. Khan; S. M. H. Andrabi; A. Razzaq; M. N. Khan (Journal of Animal and Plant Sciences, 2019)
For the rapid genetic improvement of non-descript indigenous (Bos indicus) cattle of Azad Jammu and Kashmir through artificial insemination (AI) both in natural and induced AI program heat detection is a key. The study was undertaken to describe the duration and intensity of natural and induced estrus in indigenous heifers and cows. A total of 12 heifers and 18 cows were synchronized using the Ovsynch protocol (day 0 GnRH-1, day 7 PG, day-9 GnRH-2). In natural estrus group 8 heifers and 6 cows were utilized in this study. They were observed for total duration of estrus and standing estrus. The primary and secondary estrus signs were observed. The total duration of heat in heifers was 18.63±1.03 and 18.00±1.58 h in induced and natural group respectively. The duration of standing estrus in induced and natural groups was 10.63±0.60 and 8.25±0.73 h, respectively. In cows, the total duration of estrus in induced and natural groups was similar, whereas, the duration standing estrus was longer in induced group (9.69±0.62 h) compared to natural group (6.66±0.80 h) (P<0.05). The estrus intensity score was not affected significantly in both heifers and cows between induced and natural estrus. The duration of standing estrus in indigenous heifers and cows has been shortened in natural compared to induced estrus.
Keywords: Bos indicus; duration of estrus; natural estrus; induced heat